Determinants and relevance of internalisation of environmental management systems. (10th November 2022) - Daddi, Tiberio; Todaro, Niccolò Maria; Marrucci, Luca; Iraldo, Fabio
Abstract: The internalisation of Environmental Management Systems (EMS) is raising interest among scholars. Authors have identified it as the reason of controversial results in literature about the relation between EMS and environmental performance. Often, certified companies without an internalised system are labelled to have symbolic behaviour in environmental management. However, the literature lacks of studies aimed to identify other justifications that could influence the performance of certified companies, also in absence of an internalised EMS. This study wants to analyse the role of the environmental manager satisfaction in the internalisation of EMS and in achieving environmental performance. The paper uses data from a survey of 438 EMAS registered organisations. The results show that the managers' satisfaction positively influence the environmental reputation and competitiveness also without considering the mediating role of internalisation. The paper opens new research avenues on the understanding of the real importance of EMS internalisation and on the need to further investigate the relation between EMS and performance.